Pengaruh Perputaran Kas, Perputaran Piutang dan Perputaran Persediaan terhadap Return On Asset pada Perusahaan Kosmetik dan Barang Keperluan Rumah Tangga yang Terdaftar di Bursa Efek Indonesia - Nurfadilah Abdul Latif; Sudjinan Sudjinan; Nurlia Nurlia (Fakultas Ekonomi Universitas Balikpapan, 2022)
Nurfadilah, The Effect Of Cash Turnover, Receivable Turnover, And Inventory Turnover To The Return On Assets in Cosmetics and Household Needs Company’s that listed in indonesia stock exchange under the first advisor Drs. Sudjinan, M.Si. and second advisor Nurlia, SE., MM. This research aims to know the influence of simultaneus or partially variable Cash Turnover, Receivable Turnover, And Inventory Turnover To The Return On Assets Of Cosmetics and Household Needs Compse is greater than . While the test result that partially variable Receivable Turnover has a dominant influence on the company’s Return On Assets against Cosmetics and Household Needs Company’s that are listed on the indonesia stock exchange because of the Receivable Turnover has the value and the partial r most large compored to other variable both.